Management of Femoral Pseudoaneurysms in Intravenous Drugs Users - A bubble trouble - Pradhan, Sumita; Shrestha, K (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: Femoral pseudoaneurysm in the intravenous drug users is a challenge to the treating surgeon. Surgical options range from ligation with excision to reconstruction using various kinds of grafts. However there is no generalized consensus on the optimal surgical treatment and the controversy persists. Methods: Medical charts of 10 consecutive patients presenting with infected femoral pseudoaneurysm of the lower limbs in emergency department,who underwent surgery in Bir Hospital from Jan 2008 to Dec 2010 were retrospectively analyzed. The patients were divided into two groups randomly based on the surgical management they had received. First was the reconstructive group and the second group underwent simple ligation of the femoral artery and excision of the pseudoaneurysm. Results: All cases underwent emergency surgery. Extra anatomical Iliofemoral bypass was done in total of 7 cases, of which polytetrafluroethylenePTFE graft in 5 and Vein graft in 2 cases. Ligation of the femoral artery and excision of the pseudoaneurysm was done in 3 cases. In the reconstructive group 2 cases had to be operated twice for bleeding, 1 with PTFE graft and other with vein graft whereas 2 cases had late graft infection and was attributed to reinjection of drugs through the graft. All 4 cases underwent reoperation with ligation. In the second group with simple ligation and excision except for mild claudication, there were no other major complications. There was no mortality in both the groups. Conclusion: Intravenous drug users have high tendency to reuse femoral site for reinjection and thus arterial reconstruction maybe in jeopardy of recurrent infection and reoperation. Simple ligation with debridement and excision may prove to be a better option in cases of emergency surgery followed by delayed reconstruction if needed.